Coarse-grained modeling for predicting the piezoresistive response of CNT-elastomer nanocomposite - Yeo, Jinwook; Jung, Jiyoung; Ryu, Seunghwa (Frontiers in Materials, 2023)
Significant attention has been paid to developing highly flexible and highly stretchable strain sensors due to the increasing demand for wearable devices such as motion-capturing devices and health-monitoring devices. Especially, carbon nanotube (CNT) network-based elastomeric sensors have been studied extensively for their unique strong piezoresistive response under large deformation. Despite its importance for the facile design of sensors, the effect of length and volume fraction of CNT on the piezoresistivity over a large strain range has not been fully uncovered. In this study, by combining coarse-grained molecular statics (CGMS) simulations and efficient percolation network analysis, we investigate the piezoresistive response of the CNT network for a wide range of the length and volume fraction and visualized the CNT network topology to understand the mechanism behind the piezoresistivity response. Based on the set of calculations, we obtain the design map of stretchability and sensitivity for the CNT-elastomer nanocomposite sensors over a wide range of design parameters of CNT, which can be used to fabricate the strain sensor with a desired performance.